WILL SOCIAL NETWORKS SERVE AS A TOOL FOR ECOLOGY RESEARCH IN THE FUTURE? THE CASE OF THE PRESENCE OF LEOPARDUS COLOCOLA (FELIDAE, CARNÍVORA) IN CHILE - Chávez-Villavicencio, César Lautaro (2021)
Social networks revolutionized communication in the world, transformed the media into broadcast media where users shared information of different kinds. For example, users of social networks in Chile posted photographs of wildlife including felines such as Leopardus colocola (Molina, 1872). If social media users published their findings in a selfless, altruistic and honest way, then they will serve as a tool for ecology research in the future. Under this consideration, the objective of this work was to establish if social networks can be constituted as a data source to know sites of presence of L. colocola in Chile, in comparison with the records published in scientific media. Considering that the privacy and use policies allow the use of the information from the networks, between January and April 2021, Facebook, Instagram, YouTube and Twitter were searched for publications about the species. A location coordinate was approximated using Googe Earth Pro. Additionally, publications in scientific journals and the Global Biodiversity Information Facility database were searched. 57 records of L. colocola were found in social networks, 21 in Global Biodiversity Information Facility and seven in scientific publications. Seven records from central Chile were located outside the known geographic range. Social networks served and will serve in the future, as a tool for research in ecology, especially if it is viewed under the concept of citizen science and under the assumption of altruism and honesty. The records of L. colocola published on social networks by users in Chile, undoubtedly contributed to the knowledge of new sites of presence of the species.